Dynamic analysis of immune status in patients with intracranial germ cell tumor and establishment of an immune risk prognostic model - Wang, Hairong; Huang, He; Lin, Xiaoping; Chi, Peidong; Chen, Hongyu; Chen, Jiangen; Mou, Yonggao; Chen, Zhongping; Yang, Qunying; Guo, Chengcheng (Frontiers in Immunology, 2022)
Introduction: Immune status was evaluated by means of lymphocyte subset counts and immune factors in cancer. This study analyzed the peripheral blood immune index and survival outcomes in intracranial germ cell tumor (iGCT) patients. Methods: Peripheral blood lymphocyte subset counts and levels of interleukin (IL)-2, IL-4, IL-6, IL-10, tumor necrosis factor (TNF), and interferon-γ (IFN) from 133 iGCT patients were collected and retrospectively analyzed. Their clinical information was extracted from the hospital database, and prognosis was confirmed by telephone visit. Patients (n=11) underwent prospective review and their samples of peripheral blood lymphocytes were verified. Results: A total of 113 (84.2%) patients received comprehensive treatments, including 96 standard therapy (combination of full course chemotherapy and radiology with or without surgery) and 17 comprehensive but non-standard therapy (either without full course chemotherapy or with non-standard radiotherapy) and 98 (73.7%) reached complete or partial response. T lymphocytes (CD3+), cytotoxic T cells (CD3+CD8+ or Tc), and B lymphocytes (CD19+) decreased (p=0.047, p=0.004, and p<0.001, respectively), while activated cytotoxic T lymphocytes (CD8+CD25+) and IFN increased (p<0.001 and p=0.002, respectively) after treatment. Median survival was 45.33 months, and patients with increased Tc cells and activated Tc cells as well as IFN presented encouraging outcomes (p=0.039, p=0.041, and p=0.017 respectively). Regression analysis showed that non-increased Tc cells and non-increased activated Tc cells were independent factors of poor prognosis (p=0.016, HR=3.96, 95%CI=1.288-12.20; p=0.002, HR=4.37 95%CI= 1.738-10.97). Standard chemo-radiotherapy was independently related to reduced risk of death(p=0.022, HR=0.19, 95%CI=0.044-0.79). Consistence was seen in a nomogram established through retro and prospective studies. An immune risk model indicated the activated group (with both increased activated T cells and IFN levels) had the best prognosis, the mildly activated type with elevated IFN levels had intermediate outcome, and patients with the silent immune status had the worst outcomes (Log rank test, p=0.011). Conclusion: Implementation of standard comprehensive treatments led to positive responses. Dynamic monitoring of peripheral blood lymphocyte subsets can be used as an auxiliary indicator for prognosis judgment.